Towards Live Migration Using Rule Trigger Secure Policies in Virtual Machines - Ragupathi, D; Santhanaarokiajohnsy, S (International Journal of Computer Sciences and Engineering, 2025)
Virtualization innovation has become commonplace in advanced information focuses and group systems, frequently referred as “Registering Clouds”. In particular, the capacity of virtual machine (VM) development brings various advantages such as higher performance, improved reasonability and flaw tolerance. Moreover, live development of VMs frequently permits workload development with a short administration downtime. However, administration levels of running applications are likely to be adversely influenced amid a live VM migration. Alternately this reason, a better understanding of its impacts on framework execution is exceedingly desirable. In this paper, we present a execution assessment on the impacts of live development of virtual machines on the execution of applications running inside Xen VMs. Results appear that in most cases, development overhead is worthy however can’t be disregarded, particularly in frameworks where administration accessibility and responsiveness are administered by strict Administration Level Understandings (SLAs). Despite that, there is a high potential alternately live development materialness in information focuses serving enterprise-class Web applications. Our results are based on a workload formed of a genuine application, covering the space of multi-level Web 2.0 applications.